1970
DOI: 10.1113/expphysiol.1970.sp002059
|View full text |Cite
|
Sign up to set email alerts
|

Receptive Field Properties of Single Units From the Visual Projection to the Ipsilateral Tectum in the Frog

Abstract: The receptive field characteristics of single visual units in the ipsilateral tectum of the frog were investigated. In contrast to units in the contralateral tectum, ipsilateral units all responded to small visual stimulus objects and gave a sustained response to a small stationary black disk. Inhibition of this sustained response by a moving edge some distance from the ERF could be demonstrated and was more marked than with contra-lateral units. Some of the deeper ipsilateral units, in addition to the propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Background‐ and context‐dependent effects on the spike discharge of tectal neurons have been reported in several studies in anurans (Grüsser‐Cornehls et al. , 1963; Gaze & Keating, 1970; Tsai & Ewert, 1988). In the study of Plethodon by Schülert & Dicke (2005), suppression of spike discharges on presentation of a cricket dummy (the SI, also used in the present study) inside the ERF of a tectal neuron was found when another prey stimulus was moved outside the ERF.…”
Section: Discussionmentioning
confidence: 92%
“…Background‐ and context‐dependent effects on the spike discharge of tectal neurons have been reported in several studies in anurans (Grüsser‐Cornehls et al. , 1963; Gaze & Keating, 1970; Tsai & Ewert, 1988). In the study of Plethodon by Schülert & Dicke (2005), suppression of spike discharges on presentation of a cricket dummy (the SI, also used in the present study) inside the ERF of a tectal neuron was found when another prey stimulus was moved outside the ERF.…”
Section: Discussionmentioning
confidence: 92%
“…A topographical representation of the superior portion of the anterior binocular visual field has been found on the rostral optic tectum in which an exact retinal correspondence of the two multi-unit, monocular receptive fields was reported [Gaze and Jacobson, 1962], The ipsilateral tectal projection is not a direct retinal projection but is thought to be derived, multisynaptically, from the contralateral tectum [Keating and Gaze, 1970], Earlier single-unit studies have characterized some of the properties of the direct contralateral fibers and the ipsilateral afferents, but without consideration of the spatial and temporal relationships between the two [Maturana et al, 1960;Grusser and Grusser-Cornehls, 1970;Gaze and Keating, 1970]. The demonstration of binocularly-driven neurones deep in the rostral optic tectum [Fite, 1969] suggests the possibility of a functional capacity for binocular vision in the frog, although stereoscopic depth perception has yet to be proven or disproven [Fite, 1974;Ingle, 1972].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that rostrocaudal gradients play little or no role in the placement of these arbors and that a random process, assisted by spontaneous activity in local tectal circuitry, helps to establish the arbors and to maintain TZ size. There may be considerable amounts of spontaneous activity in the axons of dark‐reared animals, particularly because several classes of both retinotectal and isthmotectal axons fire at high levels in response to low light levels under normal circumstances (Gaze and Keating,1970; Chung et al,1974), and isolated adult retinas display spontaneous ganglion cell firing in the dark (J.A. Demas, H.L.…”
Section: Discussionmentioning
confidence: 99%